Stimulating Cognitive Abilities to Recognize Animals through Digital Games: PUZOOVA (Puzzle Zoo Adventure) BookWidgets Based on Kindergarten B Children - Amalus Sholeha; Wuri Astuti (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Cognitive ability is an important aspect of early childhood development, particularly in recognizing the surrounding environment, including animals. Conventional learning methods, which are generally one-way in nature, are considered less effective in optimizing children's active engagement. This study aims to describe the implementation of the PUZOOVA (Puzzle Zoo Adventure) Digital Game in stimulating the cognitive ability of kindergarten children to recognize animals. The study was conducted with Group B kindergarten children aged 5–6 years at PAUD Kamilia. This research employed a descriptive qualitative approach involving 10 Group B kindergarten children as participants. Data were collected through participatory observation, unstructured interviews, and documentation. The findings indicate that the use of the PUZOOVA Digital Game had a significant positive impact on children's cognitive ability to recognize animals. A total of 90% of the children were able to recall animal names after the activity (categorized as Very Well Developed), while 80% demonstrated high levels of enthusiasm and active participation. The use of real animal images in an interactive digital puzzle format was proven to broaden children's cognitive knowledge, enhance logical reasoning, improve hand-eye coordination, and develop problem-solving skills in an enjoyable and meaningful way.